The injectable neurostimulator: an emerging therapeutic device. Issue 7 (July 2015) - Li, Xiaolong; Serdijn, Wouter A.; Zheng, Wei; Tian, Yubo; Zhang, Bing
Highlights Injectable neurostimulators (InNSs) for clinical use are necessary to avoid the side effects of the dominant bulky implantable neurostimulator. The concept, implementation challenges, and development trends of the InNS are illustrated in detail. The new generation of InNSs can be powered from a microbattery, a radio-frequency energy harvester, or an inductive coupling link. Obstacles include the implementation of injectable batteries, injectable antennas, and radio-frequency energy harvesters; the realization of InNSs also awaits breakthroughs in soft and bendable materials, reliability, and the mode of injection.